2001
DOI: 10.1128/mcb.21.21.7416-7428.2001
|View full text |Cite
|
Sign up to set email alerts
|

Common Regulation of Growth Arrest and Differentiation of Osteoblasts by Helix-Loop-Helix Factors

Abstract: Cellular differentiation entails the coordination of cell cycle arrest and tissue-specific gene expression. We investigated the involvement of basic helix-loop-helix (bHLH) factors in differentiation of osteoblasts using the human osteoblastic cell line MG63. Serum starvation induced growth arrest at G 1 phase, accompanied by expression of cyclin-dependent kinase inhibitor p21 WAF1/Cip1 . Reporter assays with the p21 gene promoter demonstrated that the combination of E2A (E12 or E47) and coactivator CBP was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 69 publications
8
98
0
1
Order By: Relevance
“…Although the function of TWIST is not fully established at the molecular level, recently TWIST has been indicated as a potential oncogene interfering with p53-related pathways leading to preventing myc-induced apoptosis in mouse embryonal fibroblasts (Maestro et al, 1999). TWIST is also found to be involved in the suppression of differentiation and protection of apoptosis through inhibition of p21 Waf1 via both p53-dependent and -independent pathways (Funato et al, 2001;Hjiantoniou et al, 2003). More recently, the antiapoptotic function of TWIST has been indicated through modulating NFkB pathways, and loss of TWIST expression leads to sensitization to TNFainduced apoptosis (Sosic et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the function of TWIST is not fully established at the molecular level, recently TWIST has been indicated as a potential oncogene interfering with p53-related pathways leading to preventing myc-induced apoptosis in mouse embryonal fibroblasts (Maestro et al, 1999). TWIST is also found to be involved in the suppression of differentiation and protection of apoptosis through inhibition of p21 Waf1 via both p53-dependent and -independent pathways (Funato et al, 2001;Hjiantoniou et al, 2003). More recently, the antiapoptotic function of TWIST has been indicated through modulating NFkB pathways, and loss of TWIST expression leads to sensitization to TNFainduced apoptosis (Sosic et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 3a, TWIST mRNA and protein expressions were 4.0-and 5.2-fold higher in HNE1-T3 cells as compared to HNE1 cells, respectively, which confirms the CGH results and indicates a TWIST gene amplification in HNE1-T3 cells. Since p53, p21 Waf1 , MDM2, Bax proteins have been reported to be downstream factors of the TWIST protein (Maestro et al, 1999;Funato et al, 2001;Yousfi et al, 2002), we next studied the expression of these proteins in HNE1-T3 and HNE1 cells. As shown in Figure 3b, p53, p21 Waf1 protein levels were low in HNE1-T3 cells, but MDM2 levels were high, which agrees with a previous study that TWIST may negatively interfere with the p53 tumour suppressor pathway (Maestro et al, 1999).…”
Section: Identification and Characterization Of Twist Gene Amplificatmentioning
confidence: 99%
“…Previous reports have identified Twist-1 and Twist-2 expression in different murine osteoblastic cell lines, and have shown that both genes are downregulated during osteogenic differentiation in vitro [14,20,[23][24][25]. Glackin and colleagues reported that enforced expression of either Twist-1 or Twist-2 in human osteosarcoma cell lines inhibited their ability to undergo osteoblastic maturation, whereas overexpression of Twist-1 or Dermo-1 antisense increased bone cell maturation [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Twist has been shown to be involved in several pathways that control tumor cell growth, apoptosis, differentiation and epithelial-mesenchymal transition (Maestro et al, 1999;Funato et al, 2001;Valsesia-Wittmann et al, 2004;Yang et al, 2004;Alexander et al, 2006). Moreover, Twist inhibits the p53-mediated response to cellular stress (Stasinopoulos et al, 2005).…”
Section: Introductionmentioning
confidence: 99%